Philosophical reflections in The Way publications - Ejeh, Ameh A. (Lagos London Bahiti & Dalila, 2021)
Selected articles originally published in The way newspaper between 2012 and 2021.
"10th anniversary memento"--Volume 2, title page.
Keywords: Idoma (African people)